CLINIC AND EPIDEMIOLOGICAL CHARACTERISTICS OF «ATYPICAL PNEUMONIA» FOCUS IN BLAGOVESHCHENSK, AMUR REGION - V. T. Smirnov; N. N. Zhukova; V. A. Pivovarov; O. F. Goryachkina; I. I. Lakotsenina (Acta Biomedica Scientifica, 2020)
The substantiating of SARS diagnosis in patients (Blagoveshchensk, Amur Region) is presented. The diagnosis was based on the results of clinical picture, epidemiological anamnesis and inquiry, and laboratory study of the patient’s blood and nasopharyngeal washes with the help of ELISA and PCR.